Global genomic epidemiology of chromosomally mediated non-enzymatic carbapenem resistance in Acinetobacter baumannii: on the way to predict and modify resistance - Nageeb, Wedad M.; AlHarbi, Nada; Alrehaili, Amani A.; Zakai, Shadi A.; Elfadadny, Ahmed; Hetta, Helal F. (Frontiers in Microbiology, 2023)
Introduction Although carbapenemases are frequently reported in resistant A. baumannii clinical isolates, other chromosomally mediated elements of resistance that are considered essential are frequently underestimated. Having a wide substrate range, multidrug efflux pumps frequently underlie antibiotic treatment failure. Recognizing and exploiting variations in multidrug efflux pumps and penicillin-binding proteins (PBPs) is an essential approach in new antibiotic drug discovery and engineering to meet the growing challenge of multidrug-resistant Gram-negative bacteria. Methods A total of 980 whole genome sequences of A. baumannii were analyzed. Nucleotide sequences for the genes studied were queried against a custom database of FASTA sequences using the Bacterial and Viral Bioinformatics Resource Center (BV-BRC) system. The correlation between different variants and carbapenem Minimum Inhibitory Concentrations (MICs) was studied. PROVEAN and I-Mutant predictor suites were used to predict the effect of the studied amino acid substitutions on protein function and protein stability. Both PsiPred and FUpred were used for domain and secondary structure prediction. Phylogenetic reconstruction was performed using SANS serif and then visualized using iTOL and Phandango. Results Exhibiting the highest detection rate, AdeB codes for an important efflux-pump structural protein. T48V, T584I, and P660Q were important variants identified in the AdeB-predicted multidrug efflux transporter pore domains. These can act as probable targets for designing new efflux-pump inhibitors. Each of AdeC Q239L and AdeS D167N can also act as probable targets for restoring carbapenem susceptibility. Membrane proteins appear to have lower predictive potential than efflux pump-related changes. OprB and OprD changes show a greater effect than OmpA, OmpW, Omp33, and CarO changes on carbapenem susceptibility. Functional and statistical evidence make the variants T636A and S382N at PBP1a good markers for imipenem susceptibility and potential important drug targets that can modify imipenem resistance. In addition, PBP3_370, PBP1a_T636A, and PBP1a_S382N may act as potential drug targets that can be exploited to counteract imipenem resistance. Conclusion The study presents a comprehensive epidemiologic and statistical analysis of potential membrane proteins and efflux-pump variants related to carbapenem susceptibility in A. baumannii, shedding light on their clinical utility as diagnostic markers and treatment modification targets for more focused studies of candidate elements.